International legal regulation of environmental protection in the context of the interrelationship between the principles of international environmental law and international economic law (Journal of actual problems of jurisprudence, 2018)
The article gives the concept of the principles of international environmental law, their interaction with the principles of international economic law, as well as general description of main international legal documents in the field of environmental protection. Currently, to stabilize economic development, great attention is given to the rational use of natural resources and the emergence of new model of management. To solve this problem, important legal instrument is the contractual procedure for acquiring the rights of nature use, which is properly enshrined in both international and national natural resource legislation. Existing problems at the international level in the use of environmental protection are of different nature, which should be taken into account in the implementation of legal regulation. The purpose of the study is to identify specifics of the interaction between international environmental and international economic law, justification of the need for the development, as well as the application of the norms, of specified branches of international law in the context of their interaction. As a result of writing the article, authors put forward and substantiated theoretical provisions concerning the need for comprehensive application of the norms of international environmental and international economic law. Key words: environmental law, economic law, interaction, international regulation, principles of law.